2018
DOI: 10.1007/s00417-018-4030-9
|View full text |Cite
|
Sign up to set email alerts
|

Pulse waveform analysis on temporal changes in ocular blood flow due to caffeine intake: a comparative study between habitual and non-habitual groups

Abstract: The experiment results demonstrated caffeine does modulate OBF significantly and response differently in non-habitual and habitual groups. Among all ten parameters, MBR and BOT were identified as the suitable biomarkers to differentiate between the two groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Individual characteristics such as sex, early atherosclerotic changes, glaucoma severity, and systemic hemodynamic values are shown to be related to parameters that can be extracted from the pulse waveform. [69][70][71][72][73] One can even differentiate between habitual and nonhabitual coffee drinkers based on temporal changes in ocular blood flow. 72 Many studies using LSCI are available within the field of ophthalmology since this way the effect on the cardiovascular system can be studied in great detail, for example, diabetes.…”
Section: Ophthalmologymentioning
confidence: 99%
See 1 more Smart Citation
“…Individual characteristics such as sex, early atherosclerotic changes, glaucoma severity, and systemic hemodynamic values are shown to be related to parameters that can be extracted from the pulse waveform. [69][70][71][72][73] One can even differentiate between habitual and nonhabitual coffee drinkers based on temporal changes in ocular blood flow. 72 Many studies using LSCI are available within the field of ophthalmology since this way the effect on the cardiovascular system can be studied in great detail, for example, diabetes.…”
Section: Ophthalmologymentioning
confidence: 99%
“…[69][70][71][72][73] One can even differentiate between habitual and nonhabitual coffee drinkers based on temporal changes in ocular blood flow. 72 Many studies using LSCI are available within the field of ophthalmology since this way the effect on the cardiovascular system can be studied in great detail, for example, diabetes. 74,75 Despite the fact that detection of an early atherosclerotic change can be useful, it could also unintentionally negatively influence the determination of another characteristic.…”
Section: Ophthalmologymentioning
confidence: 99%
“…Caffeine, in contrast, was reported to induce a vasoconstrictory response [6], to decrease ocular blood flow [7,8], and to increase vascular resistance of retrobulbar vessels [9]. Nevertheless, when comparing habitual and nonhabitual coffee drinkers, significant reductions of ocular blood flow after caffeine intake could only be detected in non-habitual coffee drinkers [10]. An explanation for this fact could be the upregulation of adenosine receptors induced by chronic intake of caffeine [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have revealed that age [8][9][10][11] and sex 8-12 are significantly correlated with the average MBR in the ONH. The change in MBR throughout the cardiac cycle is represented by waveform parameters such as blowout score (BOS) [13][14][15][16][17][18] and blowout time (BOT) 14,[19][20][21][22][23][24][25] , which are used to quantify age-dependent increases in resistivity 8 and to assess the relationship between blood flow and resistivity 26 .BOS and BOT partly reflect vascular resistance 27,28 , but their calculation requires averaging from separate images acquired for each heartbeat, and these parameters are thus strongly influenced by heart rate. Beat strength (BS) over the temporal average of the MBR (BOM) parameter, which does not depend on heart rate, was therefore devised to overcome this drawback.…”
mentioning
confidence: 99%
“…Several studies have revealed that age [8][9][10][11] and sex 8-12 are significantly correlated with the average MBR in the ONH. The change in MBR throughout the cardiac cycle is represented by waveform parameters such as blowout score (BOS) [13][14][15][16][17][18] and blowout time (BOT) 14,[19][20][21][22][23][24][25] , which are used to quantify age-dependent increases in resistivity 8 and to assess the relationship between blood flow and resistivity 26 .…”
mentioning
confidence: 99%